Citra Mubalig Kodam XIV/Hasanuddin di Media Sosial - saleh syahrir, muhammad; Muhammad Saleh Syahrir; Ramsiah Tasruddin; Rahmawati Haruna (Danudirja Setyabudi Nusantara, 2025)
This research examines Mubalig Kodam XIV / Hasanuddin's distinctive social media branding strategy for da'wah communication. The research methodology involves a qualitative approach, with data collected from interviews with five key informants and content analysis of lectures uploaded to social media on Facebook, Instagram, and TikTok in 2024 by the XIV Hasanuddin regional commander's preachers. The study unearthed three significant findings. Firstly, the innovative use of platform-specific strategies is pivotal in optimizing engagement. Facebook serves as a platform for in-depth religious discussions. On the other hand, Instagram emphasizes visual storytelling with series such as